2021
DOI: 10.1590/s1677-5538.ibju.2020.0242
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes of one-stage augmentation anterior urethroplasty: a systematic review and meta-analysis

Abstract: Objective: The objective is to summarize and characterize the long-term success of anterior augmentation urethroplasty (AU) in published series. The current literature on AU consists largely of retrospective series reporting intermediate follow-up and incompletely characterize the long term outcomes of AU. Materials and Methods: A systematic literature review was performed consistent with PRISMA guidelines to characterize long-term outcomes of AU with a minimum upper limit follow-up of 100 months. Penile/prepu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…After careful searching and reviewing, 1,175 studies were identified from the database searches. After the screening procedures and quality evaluations were applied, the original data extracted from eight studies ( 13 20 ) were included in the quantitative analysis. Figure 1 shows the screening flow chart.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After careful searching and reviewing, 1,175 studies were identified from the database searches. After the screening procedures and quality evaluations were applied, the original data extracted from eight studies ( 13 20 ) were included in the quantitative analysis. Figure 1 shows the screening flow chart.…”
Section: Resultsmentioning
confidence: 99%
“…We noticed that there was a previously published meta-analysis which also meant to evaluate penile skin flaps in the urethroplasty, however, that meta-analysis was based on the estimates calculated from Cox regression from retrospective studies, not comparison data, which may decrease the level of evidence ( 13 ). Therefore, the purpose of this study is to compare two different substitution techniques based on existing published comparison literatures.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recurrent dilation can act as a double-edged sword to further complicate this already complex pathology. Like in male urethral strictures, even in female urethral strictures, many techniques of dorsal and ventral graft/fl ap urethroplasties have been described (27,28). However, which technique is to be chosen and when is not yet standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies include patients with hypospadias in their cohorts, which is a completely different pathophysiology, being a congenital deficiency in urethral tissue as opposed to scarring of a normal urethra. [8][9][10] In addition, many approaches to the repair of a penile urethral stricture have been described. [11][12][13][14][15][16] Few studies have analyzed penile strictures after excluding hypospadias and glans-limited disease.…”
Section: Introductionmentioning
confidence: 99%